(untitled) (Research, Society and Development, 2020)
Objective: The purpose of this study is to analyze in the literature which areas of social support are available to homosexuals living with HIV / AIDS in Brazil, and how this support network is organized in society, in order to meet all essential demands for this population in facing post-diagnosis and treatment difficulties, aiming at comprehensive health care and the uniqueness of each subject. Methods: This is an integrative literature review, defined as a study that synthesizes research results that address the access and support routes for homosexuals with HIV / AIDS. To this end, the bibliographic survey was conducted at Scientific Electronic Library Online (SciELO) using the descriptors: Homosexuality, Support network, HIV / AIDS. Results: Support networks have been described in the literature as: Family, professional, instrumental, emotional, religious and popular knowledge support network. Evidence of better therapeutic adherence and quality of life for individuals who have a strengthened support network. Final considerations: The support networks for this population are organized in a disjointed manner, although they play a fundamental role in adhering to drug therapies and in maintaining the quality of life of these people.